Determining factors for the development of Nervous Orthorexia: a literature review (Research, Society and Development, 2022)
Objective: To identify the individual characteristics that can lead the adult individual to develop orthorexia nervosa. Methodology: This is a review study integrative bibliography, where searches for publications including articles were carried out in the 2006 to 2020, of which they were available in full in free access, where they addressed questions on the proposed topic. Results: It is estimated at 6.9%, and in high-risk groups are (professionals and health area) between 35% and 57.8%. Some of the studies also show a low level of education. Ademias, People who have already suffered some type of eating disorder / disorder indicate exposing orthorexia with more emphasis. Conclusion: A highest prevalence in orthorexics are health professionals, vegan people, people linked to animal protection causes and practitioners of physical exercises, having a small percentage of people outside this cycle. However, some of the studies demonstrate that there is a low level of education among individuals with orthorexia nervosa, it is worth to emphasize that more studies are needed to evidence such facts.